Efficacy of Local Corticosteroid in Idiopathic Carpal Tunnel Syndrome: A Randomized Controlled Trial (Bangladesh Journal of Neuroscience, 2013)
Background: Carpal tunnel syndrome (CTS) is a common health problem in Bangladesh especially among women. It causes significant morbidity and reduces work output in affected patients. There are few treatment options available like oral steroid, steroid injection, UST, surgical treatment etc. Considering the cost, time and consequence of surgery, short term nonsurgical management is desirable e.g. local steroid injection in the affected limb. Therefore a comparative analysis is necessary to understand the efficacy of local steroid injection.Objective: To evaluate the efficacy of local corticosteroid injection in the treatment of idiopathic carpal tunnel syndrome. Methods: 60 idiopathic CTS patients divided into two groups by randomization. One group received Inj. Triamcinolone 30 mg close to carpal tunnel and other group received oral steroids. Efficacies of treatmemt were compared in between groups.Result: The mean age of two groups were 37.5 ± 10.5 and 37.0 ± 10.24 years respectively (p = 0.272) and Majority of the patients in both treatment groups (76.7% in local steroid and 80% in oral steroid groups, p = 0.754) were female. Relief from tingling sensation and nocturnal awakening was higher in the steroid injection receivers (100% and 86.7% respectively) than that in the oral steroid receivers (6.9% and 3.4% respectively) during evaluation of outcome at the end of 3 month. End point treatment shows that none but SNAP at wrist in the local steroid group improved significantly better than that in the oral steroid group (16.2 ± 10.5 vs. 12.4 ± 6.3, p =0.039). No major side effects occurred in local steroid group except depigmentation in injected area 3 (10%) cases.Conclusion: It may be concluded that local steroid injection is an effective treatment of idiopathic carpal tunnel syndrome. But long-term efficacy of steroid injection remains uncertain.Bangladesh Journal of Neuroscience 2012; Vol. 28 (1): 10-15